Pemberdayaan Masyarakat Melalui Optimalisasi Industri Rumah Tangga Kue Kering di Kota Malang - Paramita, Pinastika Prajna; Cahyanto, Bagus; Kololikiye, Gilang Ramadan; Akbar, Jamalul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The modern era demands that business actors and micro-industry continue to monitor. This is done so that the business owned can continue to run and develop well. Micro-entrepreneurs as part of the development of future components of the economy, of course, need serious assistance in order to improve the quality of their production. The food business is an interesting branch of business and not many people have developed it, through service that is packaged in the form of community empowerment, it is expected to have an impact and benefit for mothers in the community to have the ability to produce pastries. This service is carried out in several stages which include planning, implementation, evaluation, and reporting. All stages were carried out well, stage (a) planning planning included the preparation of a service plan that took into account the results of the survey and needs analysis that had been carried out previously. (b) the implementation of the program that has been prepared in the next stage is carried out in advance at the location by implementing health, (c) evaluation is carried out with the implementation of the program that has been implemented both in good terms by supporting success and follow-up plans, and (d) reporting that includes the preparation of reports as an accountability program that has been implemented.